1945
DOI: 10.1021/ie50424a023
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Acrylate by Pyrolysis of Methyl Acetoxypropionate

Abstract: The physical test data for 40-, 60-, and 90-minute cures at 259" F. of stocks exposed to these conditions are shown in Figure 7. This chart indicates an increase in the rate of cure due to an increase in humidity, but little change in optimum physical properties.It is apparent from this investigation and the work of the Carbon Black Komenclature Committee on GR-S compounds, as well as from data on natural rubber, that the presence of moisture has an influence on the rate of cure'which cannot be ignored; consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…about 500–550 °C using LHSV in the range of 0.7–1.9 h −1 . Reported data on methyl acetoxy‐propionate pyrolysis show high acrylate selectivity around 85–100 % at 80–100 % conversion ,,…”
Section: Conversion Of Alkyl Lactates and Derivatives To Alkyl Acrylatesmentioning
confidence: 99%
See 1 more Smart Citation
“…about 500–550 °C using LHSV in the range of 0.7–1.9 h −1 . Reported data on methyl acetoxy‐propionate pyrolysis show high acrylate selectivity around 85–100 % at 80–100 % conversion ,,…”
Section: Conversion Of Alkyl Lactates and Derivatives To Alkyl Acrylatesmentioning
confidence: 99%
“…Reported data on methyl acetoxy-propionate pyrolysis show high acrylate selectivity around 85-100 % at 80-100 % conversion. [151,194,[196][197][198][199][200]…”
Section: Conversion Of Other Lactic Esters Derivatives Towards Acrylimentioning
confidence: 99%
“…Burns et al firstly used LA as raw material to produce acrylic acid (AA) in 1935 [126], and this was followed by Fisher and co-workers in the 1940s [127] and a patent led in 1949 by Atwood [128]. Holmen reported the one-step conversion of LA into acrylic acid via direct dehydration over CaSO 4 /Na 2 SO 4 heterogeneous catalyst, and 68 % yield of AA was obtained at 400°C [129].…”
Section: Lactic Acidmentioning
confidence: 99%
“…Walkup et al reported a production yield of 53% methyl acrylate from dehydration of methyl lactate using CaSO 4 catalysts [108]. Methyl lactate can react with acetic anhydride via acetoxylation at low temperature to form methyl alpha-acetoxy propionate, and the ester is subsequently pyrolyzed to methyl acrylate and acetic acid at high temperature (500-550°C) [109,110]. Lilga et al patented a process for acetoxylation of lactic acid with acetic acid and achieved a greater than 90% yield of 2-acetoxy propionic acid [109].…”
Section: Selective Dehydration Of Lactic Acid To Acrylic Acidmentioning
confidence: 99%